Global determinants of freshwater and marine fish genetic diversity - Stéphanie Manel (Nature Portfolio, 2020)
Biogeographic patterns of genetic diversity are poorly documented, especially for fish species. Here the authors show that (mitochondrial) genetic diversity has global spatial organization patterns with different environmental drivers for marine and freshwater fishes, where genetic diversity is only partly congruent with species richness.